Web Application Design and Development for Online Curry Paste Business: A Case Study of Ban Sai Luang Community, Khuan Khanun District, Phatthalung Province. - Tippracha, Patcharee; Makkhai , Sasikamon; Panyawutso, Chainun; Thepnarin, Nawaphol (Journal of Management Science Nakhonratchasima University, 2025)
This research aimed to design, develop, and evaluate user satisfaction with an online curry paste business web application for the Ban Sai Luang community, Khuan Khanun District, Phatthalung Province. A purposive sampling method was employed, consisting of two participant groups: (1) 22 users of the web application and (2) two system administrators, including the business owner and the web application administrator. The system was developed using MySQL, Xampp, and programming languages such as PHP, HTML, and CSS, following the System Development Life Cycle (SDLC) and database design principles. The study found that the developed web application effectively meets the needs of both end users and system administrators. User satisfaction with the web application was rated highest, particularly for mobile device usability (𝑥̄<!–Sv6Kpe[]–> = 4.91), followed by product search convenience (𝑥̄ = 4.86). The interface’s aesthetic design received the lowest mean score ( 𝑥̄= 4.64). For system administrators, the highest satisfaction concerned the convenience of verifying payment status ( 𝑥̄= 4.68), followed by the ease of adding, editing, and deleting products (𝑥̄ = 4.64). The lowest rating was related to the flexibility in managing promotions and discounts (𝑥̄ = 4.36). In conclusion, the developed web application for the online curry paste business effectively met user requirements, demonstrated practical suitability, and has potential as a prototype for developing similar applications to support other community-based enterprises in the future.